Atopic dermatitis complicated by berloque dermatitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
Berloque dermatitis is linked to the upgrading of melanogenesis induced by ultraviolet rays thanks to psoralenic substances contained in perfume bergamot oil and sterilization products. The drainage of the photosensitizing fluid gives rise to bizarre dermatitis, sometimes simulating a jewel (2), first erythematous and then hypermelanic. Despite the widespread presence of these substances, dermatitis is rare for the variability of exogenous factors (applied quantity, intensity and duration of exposure, presence of epidermal lesions) and individual susceptibility (1). The wavelength involved in dermatitis pathogenesis is greater than 320 nanometers. Acute dermatitis can go unnoticed in the presence of other dermatological problems as in the present case. The duration of the chronic pigmentary phase is also very variable.